PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PT FOCUS DIGISELLINDO UTAMA - Jacky, Jacky; Syaifullah, Syaifullah (LPPM Universitas Putera Batam, 2021)
This study aims to determine the effect of product quality and service quality on customer satisfaction at PT Focus Digisellindo Utama. The phenomenon of fluctuation of the customer satisfaction level for PT Focus Digisellindo Utama reflects the customer satisfaction has not been maximized. This research uses two independent variables which are product quality variable and service quality variable. The technique used in collecting data used in this research is the distribution of questionnaire using saturated sampling method, whereby the sample used in this research are amounting to 120 respondents. This research uses technical data analysis methods such as validity test, reliability test, classic assumption test, multiple linear regression analysis, determination coefficient test, and hypothesis test. The result of this research show that product quality and service quality variable partially does have positive influence and is significant towards the consumer satisfaction. Furthermore, product quality and service quality variable simultaneously does have positive influence and is significant towards the customer satisfaction of PT Focus Digisellindo Utama. Variables in this research have an influence od 98,2% towards the performance of employees. The rest 1,8% are influenced by other variables coming from outside of this research.